Aldehyde dehydrogenase‐2 (ALDH2) opposes hepatocellular carcinoma progression by regulating AMP‐activated protein kinase signaling in mice. Issue 5 (31st March 2017) - Hou, Guojun; Chen, Lei; Liu, Gang; Li, Liang; Yang, Yuan; Yan, He‐Xin; Zhang, Hui‐Lu; Tang, Jing; Yang, Ying Cheng; Lin, Ximeng; Chen, Xin; Luo, Gui juan; et al.
Abstract : Potential biomarkers that can be used to determine prognosis and perform targeted therapies are urgently needed to treat patients with hepatocellular carcinoma (HCC). To meet this need, we performed a screen to identify functional genes associated with hepatocellular carcinogenesis and its progression at the transcriptome and proteome levels. We identified aldehyde dedydrogenase‐2 (ALDH2) as a gene of interest for further study. ALDH2 levels were significantly lower at the mRNA and protein level in tumor tissues than in normal tissues, and they were even lower in tissues that exhibited increased migratory capacity. A study of clinical associations showed that ALDH2 is correlated with survival and multiple migration‐associated clinicopathological traits, including the presence of metastasis and portal vein tumor thrombus. The result of overexpressing or knocking down ALDH2 showed that this gene inhibited migration and invasion both in vivo and in vitro . We also found that ALDH2 altered the redox status of cells by regulating acetaldehyde levels and that it further activated the AMP‐activated protein kinase (AMPK) signaling pathway. Conclusion: Decreased levels of ALDH2 may indicate a poor prognosis in HCC patients, while forcing the expression of ALDH2 in HCC cells inhibited their aggressive behavior in vitro and in mice largely by modulating the activity of the ALDH2‐acetaldehyde‐redox‐AMPK axis. Therefore, identifying ALDH2 expression levels in HCC might be a useful strategy for classifying HCC patients and for developing potential therapeutic strategies that specifically target metastatic HCC. (Hepatology 2017;65:1628‐1644).